MORPHOLOGY AND STRUCTURAL CHARACTERIZATION OF HUMAN ENAMEL AND DENTIN BY OPTICAL AND SCANNING ELECTRON MICROSCOPY - Ekaterina Karteva; Neshka Manchorova-Veleva; Zhelyazko Damyanov; Teodora Karteva (Peytchinski Publishing, 2019)
Purpose: The aim of this paper is to visualize and examine the structural features of enamel and dentin by observations in optical and scanning electron microscopes. Material/Methods: Optical microscopic investigations were carried out on crown and root dentin of intact human teeth, extracted for orthodontic or periodontal reasons. The prepared samples were examined in transmitted and reflected light by Leitz Orthoplan-Pol polarizing microscope with digital image attachment using observations in plane polarized light, crossed nicols (polars) and through l-plate phase-advancing compensator. Gold-coated freshly broken pieces from the same samples were examined by Philips 515 scanning electron microscope (SEM) operated at 30 kilo electron volts (keV). Results: Transmitted light photomicrographs of enamel were obtained, showing detailed images of structural characteristics like enamel spindles, tufts, lamellae and Hunter-Shreger bands. The images from dentin visualized the lateral canals, mantle dentin, ortodentin, globular dentin and granular dentin. The SEM images showed cross-sectional and longitudinal images of the dentinal tubules, peritubular dentin and the collagen network with hydroxyapatite crystals. Conclusions: The results of this study showed that the morphostructural characteristics of the hard dental tissues could be successfully observed and studied by the main techniques of polarizing optical microscopy and SEM. The observations provided highly-contrast, detailed and informative images of enamel and dentin.